Anti-inflammatory effects of avocado peels against inflammation induced by carrageenan in mice - Eko Aprilianto; Alexander Vito Harmoni Swantika Yuan; Claudia Darantika Pradita; Phebe Hendra (Universitas Ahmad Dahlan, 2019)
The aim of this research is to investigate the anti-inflammatory activity of avocado peel against carrageenan-induced inflammation in mice. The group of mice that was used as a negative control group to test the anti-inflammatory activity of infusion and decoction (group I) were given aquadest, while the group for testing the activity of extract (group II) was given CMC-Na. The positive control group (group III) was given potassium diclofenac. Groups IV-VI were given avocado peel infusion with the following doses 667.5; 1335; and 2670 mg/kgBW respectively. Groups VII-IX were given avocado peel decoction with the same doses as the previous groups. Groups X-XII were given 830; 1670; and 3330 mg/kgBW of avocado peel extract respectively. The paw edema were measured using a digital caliper for 6 hours afterwards after carrageenan injection. There were a significant (p<0.05) reduction in paw edema at all doses of infusion, decoction, and extract of avocado peel. Based on the research, it can be concluded that the avocado peels have anti-inflammatory activities.